What to do after fame? Career aspirations and expectations of high-performance female athletes - Portela-Pino, I.; Brea-Castro, M.; Raya-González, J.; Alvariñas-Villaverde, M. (International Journal of Sport Psychology, 2023)
Heading Background: The end of a sports career requires a readjustment of habits and demands the need to plan for the medium-term future on the part of female athletes. Hypothesis: H1: Elite athletes with greater social support tend to have higher career aspirations and expectations for retirement. H2: Elite athletes with higher self-esteem tend to have higher aspirations and career expectations for their retirement. Study Design: A cross-sectional observational design was used with a purposive sampling of 243 Spanish elite athletes. Methods: The present study aims to fill a gap in the scientific literature by identifying the career aspirations and expectations of high-performance female athletes. A total of 243 elite female athletes agreed to participate in this study. Results: More than half of the female athletes combine their sporting activity with another work or training activity and do not consider it easy to find a job once they have finished their sporting career, nor do they consider that it would be useful or help them as an experience to find a job. Conclusions: We conclude with recommendations for future policy and practice and for sports psychologists to better support their athletes.